Microlysimetric quantification of water consumption in poinsettia (Euphorbia pulcherrima Willd.) - Pacheco-Hernández, Pedro; Sainz-Aispuro, Manuel de Jesús; Alia-Tejacal, Irán; Arteaga-Ramírez, Ramón; Villegas-Torres, Oscar Gabriel; Unland-Weiss, Helene Emmi Karin (Revista Mexicana de Ciencias Agrícolas, 2018)
An experimental greenhouse was conditioned in Cuernavaca, Morelos, Mexico, to carry out the production of poinsettia crop under protected ambient conditions, from August to November 2012. Giving an accurately follow for both, the climatic conditions and the phenological development of the crop. The following meteorological parameters were recorded every 15 min, inside and outside the greenhouse: Wind speed and direction, solar radiation, temperature and relative humidity. For reference, the precipitation was also measured outside the greenhouse. The irrigation requirement or evapotranspiration (ET) Real (ETr) of the poinsettia was measured with eight weighing microlysimeters in polyethylene pots 15 cm in diameter with leaf/tezontle/ coir substrate in proportion of 60:20:20, resulting at 40, 70, 150 and 122 mL day-1 at the weeks 1, 4, 10 and 13 after transplanting (DAT), respectively. Based on data from weather sensors reference ET (ETo) is estimated using the algorithm of Penman Monteith (PM) in and out of the greenhouse. The poinsettia crop coefficient (Kc) was weekly and monthly measured in the greenhouse based in the inside climate information, resulting in Kc of 0.22, 0.44, 0.54 and 0.43 at the weeks 1, 5, 11 and 13 DDT and 0.21, 0.36, 0.39 and 0.3 at months 1, 2, 3 and 4 DDT, respectively.
Keywords: crop coefficient; protected agriculture; water demand